Updated probabilistic seismic hazard assessment using Mwg (Das magnitude scale) to address moment magnitude (M) scale inaccuracies below 7.5: a case study from Northeast India - Alam-, M (NATURE PORTFOLIO, 2025)
This study uses the Das magnitude scale (Mwg) to improve probabilistic seismic hazard assessment (PSHA) in Northeast India, where traditional M scales introduce inaccuracies for events below M 7.5. The M scale is mathematically flawed in this range, being based on an equation derived for Ms less than or similar to 7.0-an inconsistency evident in the observed data. Using a unified earthquake catalog of 9,968 events, calibrated to Mwg, in conjunction with region-specific seismogenic zones and observed-data-validated ground motion models, hazard spectra were derived for 475- and 2475-year return periods. The resulting PSHA indicates maximum peak ground accelerations (PGA) of 0.908 g and 1.5405 g for 10% and 2% exceedance probabilities over 50 years, respectively. Comparative analysis revealed significant discrepancies between M and Mwg, with M overestimating ground motion by up to 40% for the 475-year return period and 20% for The 2475-year return period, particularly in regions prone to medium-range earthquakes. This overestimation of the M scale (mainly for smaller and medium earthquakes) was previously reported by Choy and Boatwright in 1995 using the Gutenberg-Richter energy equation. This issue can be effectively addressed by adopting the Mwg scale, which provides a more accurate representation of seismic energy. Furthermore, M scale underestimated PGA by up to 10% for very large magnitude events. These discrepancies, particularly overestimation in smaller and medium earthquake ranges, have critical implications for structural design. The adoption of Mwg provides a more accurate seismic hazard representation, necessitating a reevaluation of current building codes and emergency response protocols in Northeast India.